Composite current collector film and preparation method thereof

By using composite adhesive layer and nano-reinforced structure in composite fluid collecting films, the problem of insufficient bonding force between metal layer and polymer layer is solved, and higher bond strength and better battery performance are achieved, while simplifying the manufacturing process and reducing costs.

CN119840252APending Publication Date: 2025-04-18SUZHOU WEIMAI MEDICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311333742.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When the existing composite liquid collector film is used in lithium-ion batteries, the bonding force between the metal layer and the polymer layer is poor, resulting in high internal resistance of the battery, poor chemical performance, and complex manufacturing process and high cost.

Method used

The composite adhesive layer is used instead of the traditional film layer, and the nano-enhanced structure is chemically cross-linked with the composite adhesive layer to improve the bonding strength between the metal layer and the composite adhesive layer, and the composite fluid collecting film is prepared through hot pressing and chemical plating processes.

Benefits of technology

The bonding force between the metal layer and the polymer layer is significantly improved, the internal resistance of the battery is reduced, the chemical performance is improved, the manufacturing process is simplified, and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119840252A_ABST
    Figure CN119840252A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite films, and discloses a composite current collector film, which comprises a metal layer; compounding an adhesive layer; and a nano-reinforced structure; wherein the nanometer reinforcing structure is oriented by the composite adhesive layer, the nanometer reinforcing structure is distributed on the composite adhesive layer, and the nanometer reinforcing structure is chemically crosslinked with the composite adhesive layer; the metal layers are distributed on the two sides of the composite adhesive layer. The composite adhesive layer replaces a thin film adopted by an existing composite current collector, the manufacturing process and cost are reduced, meanwhile, the composite adhesive layer makes full contact with the metal coating, the bonding strength of the metal layer and the composite adhesive layer and the strength of the nano-reinforced structure polymerization composite adhesive layer can be improved, and the toughness of the composite adhesive layer is further improved. The chemical crosslinking of the nano reinforced structure and the composite adhesive layer can make the strength of the composite adhesive layer comparable to that of a polyester film or a PP film, so that the adhesive force between the composite adhesive layer and the metal layer is more excellent, the swelling rate of the adhesive layer is low, and the composite adhesive layer has excellent electrolyte resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite membranes, in particular to a composite current collector membrane and a preparation method thereof. Background Art

[0002] In the category of composite current collectors, the composite current collector structure is a composite structure of metal layer-casting polymer film-metal layer, similar to a sandwich. Most composite current collectors use expensive vacuum coating equipment to prepare a metal layer of a certain thickness by multiple vacuum evaporation on a polyester film (such as PET film) or a non-polar film (such as PP film). The composite current collector obtained by this method has a loose surface structure, poor density and uniformity, and high-temperature metal evaporation causes perforation on the film surface, resulting in a high square resistance of the current collector. When used in lithium-ion batteries, it will increase the internal resistance of the battery, thereby deteriorating the chemical properties of the lithium-ion battery. At the same time, the vacuum-coated metal particles have low adhesion to the harder polymer surface. In the complex environment inside the battery, the metal is easy to fall off from the polymer surface or oxidize and dissolve, resulting in a thinner metal layer and further increase in internal resistance.

[0003] In addition, the vacuum evaporation method must ensure that there is a thicker polymer film layer in the middle of the composite current collector before metal can be evaporated on the polymer surface. The thickness of the obtained current collector is relatively large, which is not conducive to making the battery have a higher energy density.

[0004] Although vacuum aluminized film can transfer the metal aluminum layer to the surface of the substrate with the help of a carrier film to form an aluminized film. Most of the aluminized layer is transferred to other films, and due to various factors such as the thickness of the adhesive layer and the film, it is easy to cause the peel strength to decrease. In the production process of aluminized film, a layer of adhesive dry glue with a thickness of at least 0.5 microns is applied on the film. If the thickness is too small, it cannot provide good adhesion, strength and bonding effect; if the thickness is too large, it will increase the internal resistance and low energy density.

[0005] The common point of the existing technologies is that they all require polymer films, but polymer films all have their own problems. The swelling rate of polyester films in electrolytes is relatively high, while the swelling rate of non-polar films is low, but the adhesion of non-polar films to metal layers is extremely low, and metals are easily detached from the polymer layer.

[0006] Compared with metals, polymer films are heterogeneous materials, and there is no alloying layer between the polymer and metal layers, which results in poor bonding between the metal layer and the polymer film. How to improve the bonding strength becomes one of the key core issues.

[0007] Based on this, it is necessary to design a composite current collector membrane and a preparation method thereof to improve the bonding force between the metal layer and the polymer layer. Summary of the invention

[0008] In order to overcome the above technical problems, the present invention provides a composite current collector film and a preparation method thereof, which are used to achieve the purpose of having higher structural, mechanical and chemical properties between the metal layer and the polymer layer.

[0009] To achieve the above object, the present invention provides the following technical solutions:

[0010] According to one aspect of the present invention, a composite current collector film is obtained, comprising:

[0011] Metal layer;

[0012] Composite adhesive layer; and

[0013] Nano-enhanced structures;

[0014] Wherein, the nano-enhanced structure is oriented to the composite adhesive layer, and the nano-enhanced structure is distributed in the composite adhesive layer, the nano-enhanced structure is internally cross-linked, and the nano-enhanced structure is chemically cross-linked with the composite adhesive layer;

[0015] The metal layers are distributed on both sides of the composite adhesive layer.

[0016] Preferably, the thickness of the metal layer is 0.5-2 microns;

[0017] The metal layer is copper, zinc, iron, aluminum, lithium and alloys thereof;

[0018] The metal layer is coated on the composite adhesive layer by any one of electrolytic plating, vacuum evaporation, chemical plating and liquid alkali corrosion.

[0019] Preferably, the thickness of the composite adhesive layer is 2-6 microns;

[0020] The composite adhesive layer comprises at least the following components in percentage by mass:

[0021] 70-80% adhesive, 5-15% reinforcing material, 5-15% curing agent and 0.3-5% rheological additive;

[0022] Wherein, the adhesive is maleic anhydride or carboxylic acid modified polyolefin;

[0023] The reinforcing material is a rod-shaped, anisotropic, reactive plant-type nanocrystal;

[0024] The curing agent is any one of isocyanate, epoxy, amino resin, oxazoline, zinc powder and aziridine;

[0025] The active groups in the reinforcing material react with the curing agent to crosslink.

[0026] Preferably, the adhesive is any one of water-based, solvent-based or solid resin;

[0027] The plant-based nanocrystal is any one of a hydroxyl-based plant-based nanocrystal, a carboxyl-based plant-based nanocrystal, a sulfonic acid-based plant-based nanocrystal, and an amino-based plant-based nanocrystal;

[0028] The aspect ratio of the plant-based nanocrystals is greater than 8:1;

[0029] Preferably, the reinforcing material is oriented in a certain direction in the composite adhesive layer, and the orientation direction is fixed in situ by removing the solvent or applying an external oriented force.

[0030] According to another aspect of the present invention, a method for preparing a composite current collector film is obtained, comprising the following steps:

[0031] Step S10, preparing a carrier metal foil;

[0032] Step S20, preparing a composite adhesive layer solution;

[0033] Step S30, using a microfluidic coating head to coat the composite adhesive layer solution prepared in step S20 on the surface of the carrier metal foil prepared in step S10, with a coating thickness of 2-8 microns, to obtain a composite adhesive layer;

[0034] Step S40, drying and shaping the composite adhesive layer obtained in step S30 to obtain a single-sided composite layer;

[0035] Step S50, hot-pressing the single-sided composite layer obtained in step S40 and the carrier metal foil in step S10, and peeling it from the carrier to obtain a metal layer-polymer composite adhesive layer-metal layer composite current collecting layer;

[0036] Step S60, soaking or coating the surface of the metal layer composite current collecting layer of the metal layer-polymer composite adhesive layer-metal layer composite current collecting layer obtained in step S50 with a passivating agent, wherein the dry film thickness of the passivating agent is 5-500 nanometers;

[0037] Step S70, aging the product obtained in step S60 to obtain a composite current collector.

[0038] Preferably, in step S10, the preparation method of the carrier metal foil is:

[0039] A nickel-chromium passivation coating is applied to the surface of the carrier metal, with a coating thickness ranging from 2 to 50 nanometers.

[0040] Preferably, in step S30, the gap diameter of the micro-controlled flow in the micro-controlled coating head is 0.5-20 microns.

[0041] Preferably, in step S40, the drying of the composite adhesive layer satisfies the following conditions:

[0042] The drying temperature is 120-160°C and the drying time is 1-5 minutes, until the solvent of the composite adhesive layer is dried and the plant-type nanocrystals are fixed in situ.

[0043] Preferably, in step S70, the aging satisfies the following conditions:

[0044] The aging temperature is 50-130°C, and the aging time is 5-48h, until the oriented plant-type nanocrystals and the glue are fully cross-linked, and then cooled to room temperature.

[0045] According to another aspect of the present invention, a method for preparing a composite current collector film is also obtained, comprising the following steps:

[0046] Step S100, preparing a composite adhesive layer solution;

[0047] Step S200, maintaining the electric field or magnetic field, using a microchannel coating head to coat the composite adhesive layer solution on the release film, and drying and shaping to obtain a composite adhesive layer;

[0048] Step S300, placing the composite adhesive layer obtained in step S200 into a solution containing SnCl2 and Pd, soaking it at room temperature for 3 minutes, then washing it with alkaline water with a pH value of 9 for 1 minute, and then taking it out and washing it with water;

[0049] Step S400, placing the composite adhesive layer processed in step S300 into a chemical plating metal salt solution at 30-60°C to react, controlling the thickness of the metal layer to be 0.5-2 microns, taking it out, washing it with water, and air-drying it to obtain a composite current collector metal layer;

[0050] Step S500, soaking or coating the surface of the composite current collector metal layer obtained in step S400 with a passivating agent, wherein the thickness of the dry film of the passivating agent is controlled to be 5-500 nanometers;

[0051] Step S600, aging at 50-130°C for 5-48 hours until the oriented plant-type nanocrystals and the glue are fully cross-linked, and then cooling to room temperature to obtain a composite current collector.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] In the present invention, the composite adhesive layer replaces the film used in the existing composite current collector, reducing the manufacturing process and cost. At the same time, the composite adhesive layer is fully in contact with the metal coating, which can improve the bonding strength between the metal layer and the composite adhesive layer, the nano-enhanced structure polymerizes the composite adhesive layer strength, and further improves the toughness of the composite adhesive layer. The chemical cross-linking of the nano-enhanced structure and the composite adhesive layer can make the strength of the composite adhesive layer comparable to that of a polyester film or a PP film, making the adhesion between the composite adhesive layer and the metal layer more excellent, the adhesive layer swelling rate is low, and has excellent electrolyte resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 A schematic diagram of the structure of a composite current collector film in one embodiment of the present invention;

[0055] Figure 2 A structural diagram of a microfluidic coating head in a method for preparing a composite current collector membrane in one embodiment of the present invention;

[0056] Figure 3 A flow chart of a method for preparing a composite current collector film in one embodiment of the present invention;

[0057] Figure 4 The present invention is a flow chart of a method for preparing a composite current collector membrane in another embodiment of the present invention.

[0058] In the figure: 1. Metal layer; 2. Composite adhesive layer; 3. Nano-enhanced structure. DETAILED DESCRIPTION

[0059] The present invention is described in detail below with reference to the accompanying drawings and embodiments.

[0060] Embodiment 1:

[0061] In conjunction with the accompanying drawings, a composite current collector film includes: a metal layer 1, a composite adhesive layer 2, and a nano-enhanced structure 3. Among them, the nano-enhanced structure 3 is oriented to the composite adhesive layer 2, and the nano-enhanced structure 3 is distributed in the composite adhesive layer 2, the nano-enhanced structure 3 is internally cross-linked, and the nano-enhanced structure 3 is chemically cross-linked with the composite adhesive layer 2; the metal layer 1 is distributed on both sides of the composite adhesive layer 2.

[0062] Specifically, the composite adhesive layer 2 replaces the film used in the existing composite current collector, reducing the manufacturing process and cost. At the same time, the composite adhesive layer 2 is fully in contact with the metal coating, which can improve the bonding strength between the metal layer 1 and the composite adhesive layer 2, and the nano-enhanced structure 3 polymerizes the composite adhesive layer strength, and further improves the toughness of the composite adhesive layer. The chemical cross-linking of the nano-enhanced structure 3 and the composite adhesive layer 2 can make the strength of the composite adhesive layer 2 comparable to that of a polyester film or a PP film, making the adhesion between the composite adhesive layer 2 and the metal layer 1 more excellent, the adhesive layer swelling rate is low, and has excellent electrolyte resistance.

[0063] In the present invention, the thickness of the metal layer 1 is 0.5-2 microns, which is used to control the overall thickness of the composite current collector film and ensure that the metal layer 1 and the composite adhesive layer 2 have a bonding strength that meets the requirements;

[0064] The metal layer 1 is copper, zinc, iron, aluminum, lithium and alloys thereof, so that the composite current collector film is used in the battery without affecting the electrochemical performance too much, and the electrolyte resistance is also good;

[0065] The metal layer 1 is coated on the composite adhesive layer 2 by any one of electrolytic plating, vacuum evaporation, chemical plating and liquid alkali corrosion, thereby achieving various manufacturing process requirements.

[0066] Furthermore, the thickness of the composite adhesive layer 2 is controlled to be 2-6 microns;

[0067] The composite adhesive layer includes at least the following components in percentage by mass:

[0068] 70-80% adhesive, 5-15% reinforcing material, 5-15% curing agent and 0.3-5% rheological additive;

[0069] Wherein, the adhesive is maleic anhydride or carboxylic acid modified polyolefin;

[0070] The reinforcement material is rod-shaped, anisotropic, reactive plant-type nanocrystals;

[0071] The curing agent is any one of isocyanate, epoxy, amino resin, oxazoline, zinc powder and aziridine;

[0072] The active groups in the reinforcing material react with the curing agent to crosslink.

[0073] Preferably, the adhesive is any one of water-based, solvent-based or solid resin;

[0074] The plant-based nanocrystal is any one of a hydroxyl-based plant-based nanocrystal, a carboxyl-based plant-based nanocrystal, a sulfonic acid-based plant-based nanocrystal, and an amino-based plant-based nanocrystal;

[0075] The aspect ratio of plant-based nanocrystals is greater than 8:1;

[0076] Preferably, the reinforcing material is oriented in a certain direction in the composite adhesive layer, and the orientation direction is fixed in situ by removing the solvent or applying an external orientation force.

[0077] Embodiment 2:

[0078] Combined with Figure 3 , a method for preparing a composite current collector film, comprising the following steps:

[0079] Step S10, taking an aluminum foil with a thickness of 6 microns, first cleaning it with an acetone solvent, and then cleaning it with a 0.1 mol sodium carbonate solution for 10 minutes after air drying, passivating the surface of the aluminum foil that has been cleaned and air dried with a trivalent chromium passivator, the amount of which is 15-20 mg / ㎡, and baking it at 120°C for 30 minutes after air drying to obtain a surface passivated aluminum foil;

[0080] Step S20, mixing water-based polyolefin dispersion (Eastman Advantis TM510W), acidified plant nanocellulose (C-CNC), rheological additive (BYK 420) and curing agent (Covestro Desmodur XP 2802) were fully mixed to obtain a composite adhesive layer;

[0081] Among them, according to the weight ratio, water-based polyolefin dispersion: 75%, acidified plant nanocellulose: 10%, curing agent: 12%, rheological additive: 3%;

[0082] Step S30, using a microfluidic coating head to coat the composite adhesive layer solution prepared in step S20 on the surface of the aluminum foil prepared in step S10 to obtain a composite adhesive layer;

[0083] The microfluidic channel gap has a diameter of 0.5 micrometers and a length of 0.5 meters.

[0084] Step S40, drying and shaping the composite adhesive layer obtained in step S30, wherein the thickness of the dry adhesive is 4 microns, and a single-sided composite layer is obtained;

[0085] Step S50, hot pressing the single-sided composite layer obtained in step S40 and the aluminum foil in step S10, rolling them up, and placing them at 110° C. for aging for 2 hours;

[0086] Step S60, thinning the product in step S50 with a 10% sodium hydroxide solution, washing with deionized water, and air-drying to obtain a composite current collector having a single aluminum metal layer thickness of 0.5 microns and a polymer composite adhesive layer thickness of 2 microns;

[0087] Step S70, coating the product obtained in step S60 with a layer of trivalent chromium passivating agent with a thickness of 10 nanometers for surface treatment.

[0088] The obtained composite current collector can be used in the fields of PCB circuit boards, food packaging, and lithium battery current collectors.

[0089] Embodiment three:

[0090] According to the method in Example 2, the difference from Example 2 is that the thickness of the polymerized composite adhesive layer is 4 microns.

[0091] Embodiment 4:

[0092] According to the method in Example 2, the difference from Example 2 is that the thickness of the polymerized composite adhesive layer is 6 microns.

[0093] Embodiment five:

[0094] According to the method in the second embodiment, the difference from the second embodiment is that the thickness of the single layer of aluminum metal is 1 micron.

[0095] Embodiment six:

[0096] According to the method in the second embodiment, the difference from the second embodiment is that the thickness of the single layer of aluminum metal is 2 microns.

[0097] Embodiment seven:

[0098] A method for preparing a composite current collector film comprises the following steps:

[0099] Step S10, preparing an electrolyte consisting of a sulfuric acid-copper sulfate aqueous solution containing 100 g / L sulfuric acid and 280 g / L copper sulfate pentahydrate;

[0100] Step S20, preparing an additive consisting of 70 mg / L hydroxyethyl cellulose, 20 mg / L polyethyleneimine, 100 mol / L sodium 3-mercapto-1-propane sulfonate, 0.5 mg / L acetylene glycol and 70 mg / L hydrochloric acid ion;

[0101] Step S30, adding the additive in step S20 to the electrolyte in step S10 to form anode and cathode films, at an electrolysis current density of 40A / dm 2 , electrolyte temperature: 40°C, electrolysis to obtain a carrier copper foil with a thickness of 0.5 μm;

[0102] Step S40, coating the carrier copper foil with a Cr passivation solution with a thickness of 15-20 mg / m 2 , drying and shaping;

[0103] Step S50, water-based polyolefin dispersion (Eastman Advantis TM 510W), acidified plant nanocellulose (C-CNC), rheological additive (BYK 420), and curing agent (Desmodur XP 2802) were fully mixed;

[0104] Among them, according to the weight ratio, water-based polyolefin dispersion: 73%, plant-based nanocrystals: 12%, curing agent: 13%, rheological additive: 2%;

[0105] Step S60, coating the product of step S50 onto the surface of the carrier copper foil obtained in step S40 through a microfluidic coating head, drying and shaping, and the dry glue thickness is 4 microns;

[0106] Step S70, hot pressing the product of step S60 and the carrier copper foil obtained in step S40, rolling them up, and placing them at 110° C. for aging for 2 hours;

[0107] Step S80, peeling off the composite copper foil and the carrier in step S70, and polymerizing a composite current collector with a composite adhesive layer having a thickness of 4 microns.

[0108] Embodiment eight:

[0109] According to the method of Example 7, the difference from Example 7 is that the thickness of the single layer of copper metal is 2 microns.

[0110] Embodiment nine:

[0111] Combined with Figure 4 , a method for preparing a composite current collector film, comprising the following steps:

[0112] Step S100, water-based polyolefin dispersion (Eastman Advantis TM 510W), acidified plant nanocellulose (C-CNC), rheological additive (BYK 420), and curing agent (Desmodur XP 2802) are fully mixed to obtain a composite adhesive layer;

[0113] Among them, according to the weight ratio, water-based polyolefin dispersion: 73%, plant-based nanocrystals: 12%, curing agent: 14%, rheological additive: 1%;

[0114] Step S200, coating the composite adhesive prepared in step S100 on a PET release film with a thickness of 12 microns through a microfluidic coating head, drying and shaping, controlling the dry film thickness to be 4 microns, and after drying, peeling the composite adhesive layer from the PET and rolling it up;

[0115] Step S300, immersing the surface of the product obtained in step S200 in a solution containing 5 g / L SnCl2 for 3 min at room temperature, then immersing it in water with a pH value of 9 (adjusted with NaOH) for 1 min, then placing it in a solution containing 10 g / L NaH2PO2 at 25°C for 5 min, then taking it out and washing it with water, and the thickness of the obtained dry film is controlled to be 20 nm;

[0116] Step S400, placing the product treated in step S300 into a chemical plating electrolytic cell, plating a layer of copper foil with a thickness of 1 micron on both surfaces of the product, washing with deionized water and then drying;

[0117] Step S500, treating the surface of the product in step S400 with a Cr3+ passivation solution, rinsing with cold water, drying, and rolling up;

[0118] Step S600, aging the product in step S500 at 110°C for 6 hours, and then cooling to room temperature to obtain a composite current collector.

[0119] Comparative Example 1:

[0120] A method for preparing a composite current collector film comprises the following steps:

[0121] Step S10, firstly, wash the aluminum foil with a thickness of 6 microns with acetone solvent, air-dry it, and then wash it again with 0.1 mol sodium carbonate solution for 10 minutes, and then passivate the surface with trivalent chromium passivator to 15-20 mg / m2, and then air-dry it and bake it at 120° C. for 30 minutes to obtain the aluminum foil with surface passivation;

[0122] Step S20, water-based polyolefin dispersion (Eastman Advantis TM 510W) and curing agent (Desmodur XP2802) were fully mixed in a weight ratio of 86.2:13.8, and then coated on both sides of 3.4 μm thick PET, with a single-sided dry adhesive thickness of 1 μm;

[0123] Step S30, hot pressing the product in step S20 and the aluminum foil in step S10 on both sides, rolling them up, and then placing them at 110° C. for aging for 2 hours;

[0124] Step S40, thinning the product in step S30 with a 10% sodium hydroxide solution, washing with deionized water, and air-drying to obtain a composite current collector with a single-layer aluminum metal layer thickness of 0.5 microns and a polymer film thickness of 6.4 microns.

[0125] Comparative Example 2:

[0126] According to the method of Example 2, the difference from Example 2 is that the coating adopts the reticulated coating instead of the microfluidic coating equipment.

[0127] Comparative Example 3:

[0128] According to the method of Example 2, different from Example 2, the composite adhesive layer does not contain a curing agent.

[0129] Comparative Example 4:

[0130] According to the method of Example 2, the difference from Example 2 is that the thickness of the composite current collector is 10 microns.

[0131] Comparative Example 5:

[0132] According to the method of the fifth embodiment, the difference from the fifth embodiment is that the thickness of the single-layer copper foil is 0.3 micrometers.

[0133] Comparative Example 6:

[0134] According to the method of the fifth embodiment, the difference from the fifth embodiment is that the thickness of the single-layer copper foil is 4 microns.

[0135] Comparative Example 7:

[0136] A PET film with a thickness of 4 microns was selected, and a chromium layer with a thickness of 20 nanometers and an aluminum layer with a thickness of 1 micron were respectively deposited on two functional surfaces of the film using a continuous vacuum coating device, thereby obtaining a composite current collector having a sandwich structure of aluminum layer-insulating layer-aluminum layer.

[0137] Comparative Example 8:

[0138] A PET film with a thickness of 4 microns was selected, and chromium with a thickness of 20 nanometers was evaporated on the two functional surfaces of the film using a continuous vacuum coating device. Then, a copper metal layer with a thickness of 1 micron was water-plated to obtain a composite current collector with a sandwich structure of copper layer-polymer layer-copper layer.

[0139] In order to further illustrate the performance of the composite current collectors prepared by the methods given in different embodiments and comparative examples, Table 1 is given.

[0140] Composite current collector performance test: The performance of the composite current collector after immersion in 25°C and 85°C electrolyte for 72 hours was tested according to the following test methods.

[0141] Peel force test:

[0142] According to the peeling force GBT 8808-1988 soft composite plastic material peeling test method.

[0143] Tensile strength and elongation at break (transverse and longitudinal):

[0144] According to GBT 1040.3-2006 Plastics - Determination of tensile properties Part 3 Test conditions for films and thin strips.

[0145] Surface resistance measurement:

[0146] According to ASTM F390-2011: Standard test method for sheet resistance of metal films by collinear four-probe method.

[0147]

[0148]

[0149] Comparing Example 2 with Comparative Example 1, the peel strength of the composite adhesive layer is better than that of the metal layer due to the cast PET lamination process after electrolyte immersion test. And the tensile strength of the composite adhesive layer is higher than that of the PET composite current collector.

[0150] From the data of Examples 2-9 and Comparative Examples 1-8, it can be seen that the increase in the thickness of the conductive metal layer effectively improves the conductivity of the composite current collector, and when the thickness of the metal layer is less than 0.5 microns, the square resistance of the conductive layer increases sharply, and when the thickness of the conductive metal layer is greater than 3 microns and the thickness of the entire composite current collector is 8 microns, the purpose of reducing the thickness cannot be achieved, and as the thickness of the composite adhesive layer increases, the peel strength of the composite current collector increases, and the tensile strength and elongation at break increase. Plant-type nanocrystal orientation is conducive to improving the strength of the composite adhesive layer, and thermal crosslinking is conducive to improving the strength of the composite adhesive layer.

[0151] From the data of Examples 2-9 and Comparative Examples 1-8, it can be seen that the square resistance changes after being immersed in the electrolyte. The performance of the copper foil current collector using the composite glue layer process is better than that of the composite current collector prepared by the vacuum sputtering method.

[0152] As can be seen from Comparative Examples 4 and 6, when the thickness of the composite adhesive layer increases within a certain range, or the thickness of the metal layer is relatively large, the overall thickness of the obtained composite current collector is relatively large, greater than 10 microns, and higher than the thickness of the composite current collector obtained by the 6-micron thick copper foil currently sold on the market. In this case, it cannot play a role in reducing the volume of the composite current collector.

[0153] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various specific technical features in any suitable manner. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations. However, these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite current collector film, characterized in that: include: Metal layer (1); Composite adhesive layer (2); as well as Nano-enhanced structures (3); The nano-enhanced structure (3) is oriented in the composite adhesive layer (2), and the nano-enhanced structure (3) is distributed in the composite adhesive layer (2), the nano-enhanced structure (3) is internally cross-linked, and the nano-enhanced structure (3) and the composite adhesive layer (2) are chemically cross-linked; The metal layer (1) is distributed on both sides of the composite adhesive layer (2).

2. A composite current collector film according to claim 1, characterized in that: The thickness of the metal layer (1) is 0.5-2 micrometers; The metal layer (1) is copper, zinc, iron, aluminum, lithium and alloys thereof; The metal layer (1) is coated on the composite adhesive layer (2) by any one of electrolytic plating, vacuum evaporation, chemical plating and liquid alkali corrosion.

3. A composite current collector film and a method for preparing the same according to claim 1, characterized in that: The thickness of the composite adhesive layer (2) is 2-6 microns; The composite adhesive layer comprises at least the following components in percentage by mass: 70-80% adhesive, 5-15% reinforcing material, 5-15% curing agent and 0.3-5% rheological additive; Wherein, the adhesive is maleic anhydride or carboxylic acid modified polyolefin; The reinforcing material is a rod-shaped, anisotropic, reactive plant-type nanocrystal; The curing agent is any one of isocyanate, epoxy, amino resin, oxazoline, zinc powder and aziridine; The active groups in the reinforcing material react with the curing agent to crosslink.

4. A composite current collector film and a method for preparing the same according to claim 3, characterized in that: The adhesive is any one of water-based, solvent-based or solid resin; The plant-based nanocrystal is any one of a hydroxyl-based plant-based nanocrystal, a carboxyl-based plant-based nanocrystal, a sulfonic acid-based plant-based nanocrystal, and an amino-based plant-based nanocrystal; The aspect ratio of the plant-based nanocrystals is greater than 8:1; Preferably, the reinforcing material is oriented in a certain direction in the composite adhesive layer, and the orientation direction is fixed in situ by removing the solvent or applying an external oriented force.

5. A method for preparing a composite current collector film, used for preparing the composite current collector film according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S10, preparing a carrier metal foil; Step S20, preparing a composite adhesive layer solution; Step S30, using a microfluidic coating head to coat the composite adhesive layer solution prepared in step S20 on the surface of the carrier metal foil prepared in step S10, with a coating thickness of 2-8 microns, to obtain a composite adhesive layer; Step S40, drying and shaping the composite adhesive layer obtained in step S30 to obtain a single-sided composite layer; Step S50, hot-pressing the single-sided composite layer obtained in step S40 and the carrier metal foil in step S10, and peeling it from the carrier to obtain a metal layer-polymer composite adhesive layer-metal layer composite current collecting layer; Step S60, soaking or coating the surface of the metal layer composite current collecting layer of the metal layer-polymer composite adhesive layer-metal layer composite current collecting layer obtained in step S50 with a passivating agent, wherein the dry film thickness of the passivating agent is 5-500 nanometers; Step S70, aging the product obtained in step S60 to obtain a composite current collector.

6. The method for preparing a composite current collector film according to claim 5, characterized in that: In step S10, the preparation method of the carrier metal foil is: A nickel-chromium passivation coating is applied to the surface of the carrier metal, with a coating thickness ranging from 2 to 50 nanometers.

7. The method for preparing a composite current collector film according to claim 5, characterized in that: In step S30, the gap diameter of the micro-controlled flow in the micro-controlled coating head is 0.5-20 microns.

8. The method for preparing a composite current collector film according to claim 1, characterized in that: In step S40, the composite adhesive layer is dried to meet the following conditions: The drying temperature is 120-160°C and the drying time is 1-5 minutes, until the solvent of the composite adhesive layer is dried and the plant-type nanocrystals are fixed in situ.

9. The method for preparing a composite current collector film according to claim 5, characterized in that: In step S70, the aging satisfies the following conditions: The aging temperature is 50-130°C, and the aging time is 5-48h, until the oriented plant-type nanocrystals and the glue are fully cross-linked, and then cooled to room temperature.

10. A method for preparing a composite current collector film, used for preparing the composite current collector film according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S100, preparing a composite adhesive layer solution; Step S200, maintaining the electric field or magnetic field, using a microchannel coating head to coat the composite adhesive layer solution on the release film, and drying and shaping to obtain a composite adhesive layer; Step S300, placing the composite adhesive layer obtained in step S200 into a solution containing SnCl2 and Pd, soaking it at room temperature for 3 minutes, then washing it with alkaline water with a pH value of 9 for 1 minute, and then taking it out and washing it with water; Step S400, placing the composite adhesive layer processed in step S300 into a chemical plating metal salt solution at 30-60°C to react, controlling the thickness of the metal layer to be 0.5-2 microns, taking it out, washing it with water, and air-drying it to obtain a composite current collector metal layer; Step S500, soaking or coating the surface of the composite current collector metal layer obtained in step S400 with a passivating agent, wherein the thickness of the dry film of the passivating agent is controlled to be 5-500 nanometers; Step S600, aging at 50-130°C for 5-48 hours until the oriented plant-type nanocrystals and the glue are fully cross-linked, and then cooling to room temperature to obtain a composite current collector.

Citation Information

Patent Citations

  • Composite current collector, and lithium ion secondary battery applying current collector

    CN107221676A

  • Preparation method of chiral nematic phase porous aerogel

    CN110790976A

  • Method for enhancing performance of lithium-sulfur battery by using nanocellulose as adhesive

    CN115360353A

  • Composite current collector and preparation method thereof

    CN116072885A

  • Current collector for sodium ion secondary battery as well as preparation method and equipment

    CN116169301A